METRONIDASOL SEBAGAI SALAH SATU OBAT PILIHAN UNTUK PERIODONTITIS MARGINALIS - Regina Tedjasulaksana (Jurnal Kesehatan Gigi (Dental Health Journal), 2016)
Marginal periodontitis is one of the periodontal diseases which is characterized by the presence of periodontal pockets and tooth mobility. The most predominant bacteria in periodontal disease are anaerobic gram-negative rods such as Actinobacillus actinomycetemcomitans, Porphyromonas gingivalis, Prevotella intermedia and Bacteroides forsythus. Metronidazole is an bacteriocidal antibiotic that can be used to treat periodontitis because it can suppress the growth of Actinobacillus actinomycetemcomitans. Periodontal disease also involves aerobic bacterial infection, so the combination of metronidazole and amoxicillin is required in marginal periodontitis therapy. Both of these antibiotics also produce a synergistic effect because amoxicillin can increase the absorption of metronidazole so the concentration becomes higher in the gingival sulcus fluid and can reach the limit of MIC (minimum inhibitory concentration).